Less bank regulation, more non-bank lending - Mary Chen; Seung Jung Lee; Daniel Neuhann; Farzad Saidi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Bank deregulation in the form of the repeal of the Glass-Steagall Act facilitated the entry of non-bank lenders into the market for syndicated loans during the pre-2008 credit boom. Institutional investors disproportionately purchase tranches of loans originated by universal banks able to cross-sell loans and underwriting services to firms (as permitted by the repeal). A shock to cross-selling intensity increases loan liquidity at origination and over time. The mechanism is that non-loan exposures ensure monitoring even when banks retain small loan shares. Our findings complement the conventional view that regulatory arbitrage caused the rise of non-bank lenders.
Keywords: G20; G21; G23; G28; 330; Non-bank lending; bank deregulation; credit supply; loan liquidity; industrial organization of financial markets